Damage to skeletal muscle from eccentric exercise - Proske, U.; Allen, T. J. (Exercise and Sport Sciences Reviews, 2005)
Evidence is provided for a mechanical event as the first step in the process leading to muscle damage after a series of eccentric contractions. Aspects discussed include the decline in active tension, increase in passive tension, shift in length-tension relation, soreness, swelling, and disturbed proprioception.